Horacio y la recusatio de la elegía amorosa - Sequeiros, Víctor Agustín (2009)
Dentro del género lírico, Horacio trata de diferenciar de su propia lírica amatoria la especie erótica elegíaca de un Tibulo o un Propercio; lo hace con dos recursos de raigambre calimaquea empleados con profusión por otros poetas augusteos: la recusatio y la excusatio presentes en Odas I, 33; II, 9 y I, 38
Within the lyric genre, Horace tries to distinguish the erotic elegiac poetry of Tibullus or Propertius from his own amatory lyric poetry; he does so with two devices of Callimachean roots profusely used by other Augustan poets: recusatio and excusatio, which are present in Odes I, 33; II, 9 and I, 38
Keywords: Horacio; Recusatio; Excusatio; Lírica amorosa elegíaca; Lírica amatoria horaciana; Horace; Recusatio; Excusatio; Amatory elegiac poetry; Amatory Horatian lyric; Crítica literaria; Poesía lírica; Literatura latina; Horacio Flaco, Quinto